KEBIJAKAN HARUN AR-RASYID DAN AL-MA’MUN DALAM PENGEMBANGAN PENDIDIKAN ISLAM - Muhammad Bukhari Dasopang; Ardian Al Hidaya; Zaianal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
The policies of Harun Ar-Rashid and Al-Ma'mun in the development of Islamic education during the Abbasid Caliphate were very influential on the progress of science. Harun Ar-Rashid established the Baitul Hikmah in Baghdad, which became a centre for translation and scientific research from various civilisations. This opened up access to Greek, Persian and Indian scholarly texts, enriching the Islamic scholarship. Meanwhile, Al-Ma'mun expanded and strengthened the Baitul Hikmah, and encouraged translation and scholarship more aggressively. Problems encountered included tensions between the conservative views of traditional scholars and new scientific ideas that were perceived to threaten religious beliefs. In addition, limited funds and skilled human resources also posed challenges to the wider dissemination of education. The policies of the two caliphs led to the Golden Age of Islam, where knowledge flourished and became the foundation for the advancement of civilisation. However, this success also required a balance between innovation and conservatism to maintain harmony in a diverse society.